The Profile of T Cell Responses in Bacille Calmette–Guérin-Primed Mice Boosted by a Novel Sendai Virus Vectored Anti-Tuberculosis Vaccine - Hu, Zhidong; Gu, Ling; Li, Chun-Ling; Shu, Tsugumine; Lowrie, Douglas B.; Fan, Xiao-Yong (Frontiers in Immunology, 2018)
Insufficient induction of T cell responses by Bacille Calmette-Guérin (BCG) vaccination may underlie The kinds of vaccine-induced T cell responses that are beneficial for protection against Mycobacterium tuberculosis (Mtb) infection are not adequately defined. We had shown that a novel Sendai virus vectored vaccine, SeV85AB, was able to enhance immune protection induced by BCG in a prime-boost model. However, the profile of T cell responses boosted by SeV85AB was not determined. Herein, we show that the antigen-specific CD4+ and CD8+ T cell responses were both enhanced by the SeV85AB boost after BCG. Different profiles of antigen-specific poly-functional T cell subsets were induced in the local (lung) and systemic (spleen) sites. In the spleen, the CD4+ T cell responses that were enhanced by the SeV85AB boost were predominately IL-2 responses, whereas in the lung the greater increases were in IFN-γ- and TNF-α- producing CD4+ T cells. Nevertheless, only IL-2+TNF-α+CD8+ T subset was boosted in the lung. After a challenge Mtb infection, there were significantly higher levels of recall IL-2 responses in T cells. In contrast, IFN-γ-producing cells were barely boosted by SeV85AB. After Mtb challenge a central memory phenotype of responding CD4+ T cells was a prominent feature in SeV85AB-boosted mice. Thus, our data strongly suggest that the enhanced immune protection induced by SeV85AB boosting was associated with establishment of central memory and IL-2 secreting CD4+ T cells and confirms this Sendai virus vector system as a promising candidate to be used in a heterologous prime-boost immunization regimen against TB.